Peran Mahkamah Konstitusi dalam Sistem Ketatanegaraan Indonesia - Banjarnahor, Yabes; Afif Baadilla, Zhafran; Putra Januar, Akbar (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Constitutional Court (MK) is one of the state institutions established under the amended 1945 Constitution, with the primary authority of upholding the constitution as the highest law in Indonesia. The presence of the Constitutional Court marks the strengthening of the principles of the rule of law and democracy, particularly in the mechanism of checks and balances between state institutions. This study aims to describe the role of the MK in the Indonesian constitutional system, from judicial, political, and social perspectives. The method used is a literature study with a descriptive qualitative approach, through analysis of literature, legislation, and relevant MK decisions. The results of the study show that the Constitutional Court has a strategic role in upholding constitutional justice, including through the authority of state institutions, dissolving political parties, resolving election result disputes, and ruling on the House of Representatives' opinion regarding alleged violations of the law by the President/Vice President. In addition, the Constitutional Court also functions as the guardian of the constitution, guardian of democracy, and protector of citizens' constitutional rights. Thus, the Constitutional Court not only acts as the guardian of the constitution, but also as an important pillar in maintaining the balance of power and consolidating democracy in Indonesia.